2020
DOI: 10.1186/s12877-020-01945-6
|View full text |Cite
|
Sign up to set email alerts
|

Regional patterns and trends of hearing loss in England: evidence from the English longitudinal study of ageing (ELSA) and implications for health policy

Abstract: Background Hearing loss (HL) is a significant public health concern globally and is estimated to affect over nine million people in England. The aim of this research was to explore the regional patterns and trends of HL in a representative longitudinal prospective cohort study of the English population aged 50 and over. Methods We used the full dataset (74,699 person-years) of self-reported hearing data from all eight Waves of the English Longitudi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…These differences do not only reflect the differences in the health systems and hearing aid provisions among countries, as suggested by Sawyer et al. (2020) , but also emphasize individuals’ inability to identify their hearing difficulties as a barrier in their help-seeking process, even in countries where the hearing aids are available free of charge ( Tsimpida et al., 2020a ).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…These differences do not only reflect the differences in the health systems and hearing aid provisions among countries, as suggested by Sawyer et al. (2020) , but also emphasize individuals’ inability to identify their hearing difficulties as a barrier in their help-seeking process, even in countries where the hearing aids are available free of charge ( Tsimpida et al., 2020a ).…”
Section: Resultsmentioning
confidence: 95%
“…More recently, the term of lifestyle-related hearing loss has been added to the literature, where lifestyle refers to social practices and ways of living adopted by individuals that reflect personal, group and socioeconomic identities ( Tsimpida et al., 2019b ). The term incorporated the notion of socioacusis by including the hearing loss cases that develop due to exposures to sociospatial and modifiable lifestyle factors ( Tsimpida et al., 2020b ). In practice, many actions could be taken on several levels to make social listening safe, in terms of intensity, duration, and frequency of exposure to sounds ( WHO, 2015b ).…”
mentioning
confidence: 99%
“…The Cochrane review of Ferguson et al [ 18 ] had concluded, however, that the quality of evidence for the impact of hearing aids on the adverse effects of HL is very low; thus, large prospective studies are needed to raise the current quality of evidence [ 19 ] and further explore the potential moderating effect of hearing aids on the association between HL and depression. Given the rising prevalence of HL potentially due to social and lifestyle factors [ 2 , 20 ], it is crucial to fill the above knowledge gaps, as depression and HL are responsible for enormous public health costs, morbidity and mortality [ 21 ].…”
Section: Introductionmentioning
confidence: 99%